Five new species of the genus Diptilomiopus Nalepa, 1916 from China (Acari: Diptilomiopidae: Diptilomiopinae) - Wang, Guo-Quan; Wei, Sui-Gai; Yang, Ding (Zootaxa, 2009)
Five new Diptilomiopus species from China are described and illustrated in this paper: Diptilomiopus ambromae sp. nov. infesting Ambroma augusta (Sterculiaceae); Diptilomiopus euscaphiae sp. nov. infesting Euscaphis japonica (Staphyleaceae); Diptilomiopus ligustri sp. nov. infesting Ligustrum lucidum and L. quihoui (Oleaceae); Diptilomiopus lithocarpi sp. nov. infesting Lithocarpus glaber (Fagaceae) and Diptilomiopus ternstroemiae sp. nov. infesting Ternstroemia nitida and T. gymnanthera (Theaceae). A key to the Diptilomiopus species from China is provided.